The effects of balance training on physical fitness and skill-related performance in basketball players: a systematic review - Wang, Zhaoran; Chen, Nanting; Cao, Shudian; Gao, Lei; Geok, Soh Kim; Liu, Jia (BioMed Central, 2025)
Background: Existing evidence suggests that balance training (BT) has a positive impact on physical fitness and sports performance. However, its specific effects on basketball players have not been extensively studied. Therefore, this systematic review aims to analyze the influence of BT on the physical fitness and skill-related performance of basketball players. Method: A thorough search was conducted across four databases (Web of Science, Scopus, PubMed, and EBSCOhost) for studies published until August 24, 2024, using keywords related to BT and basketball. The quality of the included studies was assessed using the “Qualsyst” tool. Results: Thirteen studies involving 373 participants were included, focusing on BT interventions lasting a minimum of four weeks. These studies demonstrated that BT led to significant enhancements in balance, power, agility, stability, and basketball skill-related performance. Nevertheless, certain assessments such as the balance error scoring system, triple hop distance, 30-second maximal performance jump, single-leg triple hop, Y reactive agility, and maneuver running tests did not show significant improvements. Conclusion: BT proves to be a valuable intervention for improving physical fitness and skill-related performance among basketball players. However, the variability in training methods highlights the need for further research to determine the optimal BT parameters, including training volume, intensity, and duration. Additionally, future studies should explore how factors such as gender, age, and playing level influence the effectiveness of BT in basketball players.